2018
DOI: 10.1177/1687814018810249
|View full text |Cite
|
Sign up to set email alerts
|

Design and test of a self-adaptive bionic polycrystalline diamond compact bit inspired by cat claw

Abstract: Cats protract claws while hunting or pawing on the ground and retract to muscles when relaxing. Inspired by this behavior, and in order to solve the problem of short service life and low comprehensive drilling efficiency of polycrystalline diamond compact bits which results from its poor adaptability to soft-hard interbedded strata, a self-adaptive bionic polycrystalline diamond compact bit was designed, which can use the elastic element to adjust its back-rake angle according to the formation hardness to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Experimental investigations revealed that this adjustable structure possessed the capacity for adaptive rake angle adjustment in layered formations of varying hardness. This adaptability enabled the PDC cutter to maintain a smaller rake angle in softer formations and a larger rake angle in harder formations, thereby ensuring an extended lifespan of the cutter during the drilling process [26]. It is evident that by observing the advantageous structures found in nature and incorporating them into the structural design of PDC cutters, the efficiency and lifespan of the drill bit during the rock-breaking process can be effectively improved, thereby reducing drilling costs.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations revealed that this adjustable structure possessed the capacity for adaptive rake angle adjustment in layered formations of varying hardness. This adaptability enabled the PDC cutter to maintain a smaller rake angle in softer formations and a larger rake angle in harder formations, thereby ensuring an extended lifespan of the cutter during the drilling process [26]. It is evident that by observing the advantageous structures found in nature and incorporating them into the structural design of PDC cutters, the efficiency and lifespan of the drill bit during the rock-breaking process can be effectively improved, thereby reducing drilling costs.…”
Section: Introductionmentioning
confidence: 99%
“…Du et al designed a biomimetic cutter to reduce the force and energy required to cut the stalks of tea plants inspired by the special geometrical structure of the teeth of crickets [ 12 ]. Tang et al designed a self-adaptive bionic PDC bit inspired by cat claw to solve the problem of short service life and low comprehensive drilling efficiency of PDC bits [ 13 ]. Capra sibirica is the wildlife conservation at the national level.…”
Section: Introductionmentioning
confidence: 99%
“…The shape and diameter of the holes made in the rock are directly determined by the bit blades and teeth on them, the existing blades on the bit are mostly fixed structure. The hole is thus a single straight cylinder shape with a constant diameter, which is equal to the cutting dimension of the bit teeth (Tang Q.Q. et al, 2018;Wang S.N.…”
Section: Introductionmentioning
confidence: 99%